2021
DOI: 10.15537/smj.2021.42.6.20200833
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in vitiligo patients in central Saudi Arabia

Abstract: To assess the quality of life (QoL) in patients with vitiligo in central Saudi Arabia using the dermatology life quality index (DLQI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
4
7
0
3
Order By: Relevance
“…Higher quimp in patients with darker skin types than in those with fair skin was also reported 42 . Mean DLQI scores of adult vitiligo patients from studies performed in 21 different countries are presented in Figure 2 44–83 . Most studies demonstrated a moderate or small effect on patient's lives score according to the DLQI banding descriptors.…”
Section: Resultsmentioning
confidence: 86%
“…Higher quimp in patients with darker skin types than in those with fair skin was also reported 42 . Mean DLQI scores of adult vitiligo patients from studies performed in 21 different countries are presented in Figure 2 44–83 . Most studies demonstrated a moderate or small effect on patient's lives score according to the DLQI banding descriptors.…”
Section: Resultsmentioning
confidence: 86%
“…This is surprising because data from Europe and other parts of the world show that this dimension is robust, being ranked as the second-highest (10.18%) in terms of its contribution to the quality of life in Europe (Ravens-Sieberer et al, 2005;. Al-Shammari et al (2021) said there are cultural influences in Middle East countries, and in Saudi Arabia specifically, that affect the quality of life scores. Al-Mubarak et al (2011) argued that as the cultural traditions of Saudi society differ from those in the Western world, determinants, and influences on the quality of life may also be different.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…58,59 Esta enfermedad tiene una variedad de manifestaciones clínicas con cursos variables, no cuenta con criterios diagnósticos, por lo que se considera un diagnóstico de exclusión. 60 El pioderma gangrenoso es difícil de tratar ya que ningún esquema ha sido efectivo para todos los pacientes. 1 El objetivo del tratamiento es reducir la inflamación asociada que conduce a la ulceración.…”
Section: Pioderma Gangrenosounclassified
“…1 El objetivo del tratamiento es reducir la inflamación asociada que conduce a la ulceración. 60 La terapia con esteroides e inmunosupresores son el pilar del tratamiento; sin embargo, en la bibliografía se han reportado casos que responden a la terapia conjunta con esteroides y dapsona. 1,61 Actinomicetoma El actinomicetoma es una enfermedad inflamatoria granulomatosa subcutánea crónica, caracterizada por nódulos y fístulas que drenan material seroso o purulento que contiene el agente etiológico.…”
Section: Pioderma Gangrenosounclassified
See 1 more Smart Citation